Method for preparing sodium-ion battery hard carbon negative electrode material by co-pyrolysis of biomass and plastic and application of sodium-ion battery hard carbon negative electrode material

The preparation of sodium ion battery hard carbon anode material by co-pyrolysis of biomass and plastics has solved the problems of expensive raw materials, complex processes and difficult to prepare on a large scale in the prior art, and achieved high-performance and low-cost hard carbon material preparation.

CN119569027APending Publication Date: 2025-03-07SOUTH CHINA UNIV OF TECH

Patent Information

Application Number
CN202411727784.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-28
Publication Date
2025-03-07

AI Technical Summary

Technical Problem

The preparation of existing biomass hard carbon materials has the problem of expensive raw materials, complex processes and difficult to prepare on a large scale, resulting in lower ICE or poor rate performance of hard carbon materials.

Method used

By co-pyrolysis of biomass and plastics, the hard carbon negative electrode material of sodium ion battery is obtained by mixing the biomass powder with the plastic powder and adding it to the phosphate solution and stirring, then drying and carbonizing under an inert atmosphere, and finally pickling and deionized water.

Benefits of technology

This method simplifies the preparation process, reduces costs, and can be produced on a large scale. The obtained biomass hard carbon material has high specific capacitance, high head efficiency and low specific surface area, and is suitable for the negative electrode material of sodium ion batteries.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119569027A_ABST
    Figure CN119569027A_ABST
Patent Text Reader

Abstract

The invention discloses a method for preparing a sodium-ion battery hard carbon negative electrode material by co-pyrolysis of biomass and plastic and application of the sodium-ion battery hard carbon negative electrode material. The preparation method comprises the following steps: mixing biomass powder and plastic powder, adding the mixture into a phosphate solution, and stirring for 0.2-2 hours; drying the obtained mixture, and carbonizing in an inert atmosphere; and carrying out acid pickling on the obtained carbonized product, cleaning with deionized water, and drying to obtain the sodium-ion battery hard carbon negative electrode material. According to the invention, biomass and plastic are used as raw materials, an inorganic phosphate solution is used as an aperture regulator, and in the heating carbonization process, biomass and plastic co-pyrolysis greatly improves the carbon yield of pure biomass raw materials. Compared with other methods for preparing hard carbon by using biomass materials, the method is completed in one step, further modification post-treatment is not needed, and the method has the advantages of being simple, practical, low in cost and high in performance.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of biomass energy, and specifically relates to a method and application of preparing a hard carbon negative electrode material for a sodium ion battery by co-pyrolysis of biomass and plastic. Background Art

[0002] In recent years, with the large-scale application of renewable energy, low-cost sodium-ion batteries are expected to develop rapidly in many fields such as large-scale energy storage devices, communication base stations and low-speed electric vehicles. As the most commercially promising negative electrode material, hard carbon materials have the advantages of low voltage platform, high capacity, good cycle performance and abundant sources, and have attracted great attention from researchers and the industry. Among the many raw materials for preparing hard carbon materials, biomass raw materials, in particular, have the advantages of wide sources, sustainable regeneration, low pollution and low price. Using them as raw materials to prepare hard carbon materials can not only save costs, but also alleviate the environmental pollution problems caused by the incineration of large amounts of waste. Secondly, special texture structures and texture characteristics will be formed during the re-growth of biomass. After carbonization, the original microstructure can still be maintained. During the heat treatment process, a rich closed-pore structure is formed, which has excellent sodium storage performance and is expected to become the most potential new low-cost and high-performance negative electrode material for sodium-ion batteries. At present, the methods used to prepare biomass hard carbon materials include direct carbonization, hydrothermal method and template method, but the biomass hard carbon materials prepared by the above basic methods usually have the problems of low ICE or poor rate performance.

[0003] For example, the patent with publication number CN118270767A discloses a preparation method and application of sodium ion battery biomass hard carbon negative electrode materials using hydrothermal pretreatment, the purpose of which is to improve the ICE and capacity of the hard carbon material, but the operation is complicated, not only requiring hydrothermal pretreatment but also requiring the precarbonized material to be placed in an alcohol solvent for reaction, which greatly increases the complexity of the operation and the preparation cost.

[0004] For example, the patent with publication number CN115528232A discloses the preparation and application of a hard carbon material, which is obtained by soaking reed material in concentrated phosphoric acid and then drying and pyrolyzing it to obtain a P2O5 composite nitrogen-doped porous hard carbon negative electrode material. Although the specific capacitance is greatly improved, the problem of low initial efficiency of hard carbon is not solved.

[0005] In short, the preparation of hard carbon materials has high requirements for performance and cost, which requires that the preparation process should be as simple as possible. Therefore, developing a low-cost, simple process and easy-to-scale production hard carbon negative electrode material for sodium ions is of great significance to the field of energy storage. Summary of the invention

[0006] In view of the problems of expensive raw materials, complicated processes, and difficulty in large-scale preparation in the preparation method of biomass-derived hard carbon, the purpose of the present invention is to provide a method and application of preparing hard carbon negative electrode materials for sodium ion batteries by co-pyrolysis of biomass and plastics; the method of the present invention has simple steps, is cheaper, can be prepared on a large scale, and the obtained biomass hard carbon has high specific capacitance and initial efficiency. The method of the present invention is in line with the concept of green and sustainable development, and is simple, easy to implement, and low-cost, and has important application prospects in the field of energy storage. The materials prepared by the present invention have the advantages of high capacity, high initial efficiency, and low specific surface area.

[0007] The purpose of the present invention is achieved through the following technical solutions:

[0008] A method for preparing a hard carbon negative electrode material for a sodium ion battery by co-pyrolysis of biomass and plastics comprises the following steps:

[0009] (1) mixing biomass powder and plastic powder, adding the mixture into a phosphate solution and stirring for 0.2 to 2 hours;

[0010] (2) drying the mixture obtained in step (1) and carbonizing it under an inert atmosphere;

[0011] (3) The carbonized product obtained in step (2) is acid-washed, then washed with deionized water and dried to obtain a hard carbon negative electrode material for a sodium ion battery.

[0012] Preferably, the biomass powder in step (1) comprises cellulose powder or cellulose-rich waste agricultural and forestry powder;

[0013] Further preferably, the waste agricultural and forestry materials are at least one of oil tea shells, walnut shells, coconut shells, bamboo, peanut shells, straw and rice husks.

[0014] Preferably, the plastic powder in step (1) is at least one of polyethylene terephthalate PET, polypropylene PP, polyvinyl chloride PVC, and polyethylene PE.

[0015] Preferably, the mass ratio of the biomass powder to the plastic powder in step (1) is 19:1 to 1:1.

[0016] Further preferably, the mass ratio of the biomass powder to the plastic powder is 19:1.

[0017] Preferably, the phosphate in step (1) is diammonium phosphate;

[0018] Preferably, the mass ratio of the phosphate: biomass powder and plastic powder mixture in step (1) is 0.01:1 to 0.5:1.

[0019] Preferably, the stirring time in step (1) is 1 h to 2 h.

[0020] Preferably, the phosphate solution in step (1) covers the mixture of biomass powder and plastic powder.

[0021] Preferably, the drying temperature in step (2) is 60-120° C., and the stirring rate of the drying is 300-600 rpm.

[0022] Further preferably, the drying temperature is 80° C. and the drying stirring rate is 300 rpm.

[0023] Preferably, the inert atmosphere in step (2) is nitrogen or argon.

[0024] More preferably, the inert atmosphere is argon.

[0025] Preferably, the carbonization conditions in step (2) are: heating rate of 0.5 to 20° C. / min, carbonization insulation temperature of 1100 to 1500° C., and carbonization insulation time of 0.5 to 10 hours.

[0026] Further preferably, the carbonization conditions are: heating rate 5°C / min, carbonization insulation temperature 1200°C or 1300°C, and carbonization insulation time 2 hours.

[0027] Preferably, the pickling in step (3) is performed by immersing and stirring in hydrochloric acid with a concentration of 1 to 2 mol / L.

[0028] A sodium ion battery hard carbon negative electrode material is prepared by the above method and can be applied to the fields of catalysis, energy storage, etc.

[0029] Application of the above-mentioned sodium ion battery hard carbon negative electrode material in the preparation of sodium ion batteries.

[0030] The present invention uses biomass and plastic as raw materials, and an inorganic phosphate solution as an aperture regulator. During the heating carbonization process, biomass and plastic are co-pyrolyzed to greatly increase the carbon yield of pure biomass raw materials. Compared with other methods for preparing hard carbon using biomass materials, this method is completed in one step without further modification and post-processing, and has the advantages of being simple, practical, low-cost, and high-performance.

[0031] Compared with the prior art, the present invention has the following advantages and beneficial effects:

[0032] (1) The present invention uses cellulose-rich biomass materials and plastics as precursors. The raw materials are widely available and inexpensive, which can not only alleviate the excessive consumption of fossil resources and reduce production costs, but also facilitate large-scale production.

[0033] (2) The present invention reduces the use cost of cellulose and other cellulose-rich biomass materials by incorporating plastics. The preparation process is simple, easy to implement, and can be prepared on a large scale.

[0034] (3) The sodium ion battery negative electrode material prepared by the present invention has high first coulombic efficiency and high specific capacity, and has high commercial value. BRIEF DESCRIPTION OF THE DRAWINGS

[0035] Figure 1 The constant current charge and discharge curve of the electrochemical test of the hard carbon assembled sodium ion battery prepared in Example 1 (current density = 50mAg -1 ).

[0036] Figure 2 This is the thermogravimetric analysis diagram of cellulose, PET plastic, and cellulose mixed with PET plastic in Example 10.

[0037] Figure 3 This is a comparison chart of the carbon rates obtained by carbonizing cellulose powder, plastic powder, and a mixture of cellulose powder and plastic powder under the same conditions in Example 11 and the carbon rate obtained by theoretical calculation of the mixture of cellulose powder and plastic powder.

[0038] Figure 4 These are nitrogen adsorption-desorption curves of the hard carbon prepared in Examples 1 and 4. DETAILED DESCRIPTION

[0039] The present invention is further described in detail below in conjunction with the embodiments and drawings, but the embodiments of the present invention are not limited thereto. Parameter processes not specified here can be performed with reference to conventional techniques.

[0040] Example 1

[0041] (1) 10 g of a precursor mixture was obtained by mixing cellulose powder and PET plastic powder in a mass ratio of 17:3, and then poured into 50 ml of diammonium phosphate solution (the mass ratio of diammonium phosphate to the precursor mixture was 0.01:1) and stirred for 0.2 h;

[0042] (2) drying the mixture obtained in step (1) and carbonizing it at 1300° C. for a certain period of time (2 h) in an argon atmosphere to obtain a hard carbon material;

[0043] (3) Pour the hard carbon material obtained in step (2) into 1 mol of hydrochloric acid, stir and pickle, then wash with deionized water and dry, thereby obtaining a hard carbon negative electrode material for a sodium ion battery.

[0044] (4) Assemble the sodium ion battery with the sodium ion battery hard carbon negative electrode material prepared above. According to the mass ratio of 80%:10%:10%, weigh 80 mg of biomass hard carbon material powder, 10 mg of conductive carbon black, and 10 mg of carboxymethyl cellulose, add an appropriate amount (0.5 ml) of deionized water, stir for 15 minutes until it becomes a uniform slurry, use a 100 μm scraper to evenly coat it on the surface of copper (Cu) foil, dry it in a vacuum drying oven at 100 ° C for 12 hours, cut the Cu foil with active material into disc-shaped negative electrode sheets, and then transfer them to the glove box for use.

[0045] The assembly of the simulated battery was carried out in a MIKROUNA glove box filled with Ar atmosphere, using the prepared carbon material electrode as the negative electrode, commercial electrolyte 1.0 mol / L NaPF6 / EC:DMC:EMC (1:1:1) (V:V:V) as the electrolyte, and Na metal sheet as the counter electrode to assemble a 2032 button cell.

[0046] Example 2

[0047] (1) 10 g of a precursor mixture was obtained by mixing cellulose powder and PET plastic powder in a mass ratio of 17:3, and then poured into 50 ml of an ammonium phosphate solution (the mass ratio of ammonium phosphate to the precursor mixture was 0.01:1) and stirred for 0.2 h;

[0048] (2) drying the mixture obtained in step (1) and carbonizing it at 1300° C. for a certain period of time (2 h) in an argon atmosphere to obtain a hard carbon material;

[0049] (3) Pour the hard carbon material obtained in step (2) into 1 mol of hydrochloric acid, stir and pickle, then wash with deionized water and dry, thereby obtaining a hard carbon negative electrode material for a sodium ion battery.

[0050] (4) The hard carbon negative electrode material for sodium ion batteries prepared as above is used as the active material of the negative electrode material for preparing sodium ion batteries, and the specific method is the same as that in Example 1.

[0051] Example 3

[0052] (1) 10 g of a precursor mixture was obtained by mixing cellulose powder and PET plastic powder in a mass ratio of 17:3, and then poured into 50 ml of a phosphoric acid solution (the mass ratio of phosphoric acid to the precursor mixture was 0.01:1) and stirred for 0.2 h;

[0053] (2) drying the mixture obtained in step (1) and carbonizing it at 1300° C. for a certain period of time (2 h) under an inert atmosphere to obtain a hard carbon material;

[0054] (3) Pour the hard carbon material obtained in step (2) into 1 mol of hydrochloric acid, stir and pickle, then wash with deionized water and dry, thereby obtaining a hard carbon negative electrode material for a sodium ion battery.

[0055] (4) The hard carbon negative electrode material for sodium ion batteries prepared as above is used as the active material of the negative electrode material for preparing sodium ion batteries, and the specific method is the same as that in Example 1.

[0056] Example 4

[0057] (1) Pour 10 g of cellulose powder into 50 ml of diammonium phosphate solution (the mass ratio of diammonium phosphate to cellulose powder is 0.01:1) and stir for 0.2 h;

[0058] (2) drying the mixture obtained in step (1) and carbonizing it at 1300° C. for 2 h in an argon atmosphere to obtain a hard carbon material;

[0059] (3) Pour the hard carbon material obtained in step (2) into 1 mol of hydrochloric acid, stir and pickle, then wash with deionized water and dry, thereby obtaining a hard carbon negative electrode material for a sodium ion battery.

[0060] (4) The hard carbon negative electrode material for sodium ion batteries prepared as above is used as the active material of the negative electrode material for preparing sodium ion batteries, and the specific method is the same as that in Example 1.

[0061] Example 5

[0062] (1) Pour 10 g of PET plastic powder into 50 ml of diammonium phosphate solution (the mass ratio of diammonium phosphate to PET plastic powder is 0.01:1) and stir for 0.2 h;

[0063] (2) drying the mixture obtained in step (1) and carbonizing it at 1300° C. for a certain period of time (2 h) in an argon atmosphere to obtain a hard carbon material;

[0064] (3) Pour the hard carbon material obtained in step (2) into 1 mol of hydrochloric acid, stir and pickle, then wash with deionized water and dry, thereby obtaining a hard carbon negative electrode material for a sodium ion battery.

[0065] (4) The hard carbon negative electrode material for sodium ion batteries prepared as above is used as the active material of the negative electrode material for preparing sodium ion batteries, and the specific method is the same as that in Example 1.

[0066] Example 6

[0067] (1) 10 g of a precursor mixture was obtained by mixing coconut shell powder and PET plastic powder in a mass ratio of 9:1, and then poured into 50 ml of diammonium phosphate solution (the mass ratio of diammonium phosphate to the precursor mixture was 0.06:1) and stirred for 0.2 h;

[0068] (2) drying the mixture obtained in step (1) and carbonizing it at 1300° C. for a certain period of time (2 h) in an argon atmosphere to obtain a hard carbon material;

[0069] (3) Pour the hard carbon material obtained in step (2) into 1 mol of hydrochloric acid, stir and pickle, then wash with deionized water and dry, thereby obtaining a hard carbon negative electrode material for a sodium ion battery.

[0070] (4) The hard carbon negative electrode material for sodium ion batteries prepared as above is used as the active material of the negative electrode material for preparing sodium ion batteries, and the specific method is the same as that in Example 1.

[0071] Example 7

[0072] (1) 10 g of a precursor mixture was obtained by mixing coconut shell powder and PET plastic powder in a mass ratio of 9:1, and then poured into 50 ml of diammonium phosphate solution (the mass ratio of diammonium phosphate to the precursor mixture was 0.01:1) and stirred for 0.5 h;

[0073] (2) drying the mixture obtained in step (1) and carbonizing it at 1100° C. for 4 h in an argon atmosphere to obtain a hard carbon material;

[0074] (3) Pour the hard carbon material obtained in step (2) into 1 mol of hydrochloric acid, stir and pickle, then wash with deionized water and dry, thereby obtaining a hard carbon negative electrode material for a sodium ion battery.

[0075] (4) The hard carbon negative electrode material for sodium ion batteries prepared as above is used as the active material of the negative electrode material for preparing sodium ion batteries, and the specific method is the same as that in Example 1.

[0076] Example 8

[0077] (1) 10 g of a precursor mixture was obtained by mixing coconut shell powder and PET plastic powder in a mass ratio of 9:1, and then poured into 50 ml of diammonium phosphate solution (the mass ratio of diammonium phosphate to the precursor mixture was 0.01:1) and stirred for 1 h;

[0078] (2) drying the mixture obtained in step (1) and carbonizing it at 1300° C. for a certain period of time (2 h) in an argon atmosphere to obtain a hard carbon material;

[0079] (3) Pour the hard carbon material obtained in step (2) into 1 mol of hydrochloric acid, stir and pickle, then wash with deionized water and dry, thereby obtaining a hard carbon negative electrode material for a sodium ion battery.

[0080] (4) The hard carbon negative electrode material for sodium ion batteries prepared as above is used as the active material of the negative electrode material for preparing sodium ion batteries, and the specific method is the same as that in Example 1.

[0081] Example 9

[0082] (1) 10 g of a precursor mixture was obtained by mixing cellulose powder and PET plastic powder in a mass ratio of 17:3, and then poured into 50 ml of diammonium phosphate solution (the mass ratio of diammonium phosphate to the precursor mixture was 0.02:1) and stirred for 1.5 h;

[0083] (2) drying the mixture obtained in step (1) and carbonizing it at 1300° C. for 3 h in an argon atmosphere to obtain a hard carbon material;

[0084] (3) Pour the hard carbon material obtained in step (2) into 1 mol of hydrochloric acid, stir and pickle, then wash with deionized water and dry, thereby obtaining a hard carbon negative electrode material for a sodium ion battery.

[0085] (4) The hard carbon negative electrode material for sodium ion batteries prepared as above is used as the active material of the negative electrode material for preparing sodium ion batteries, and the specific method is the same as that in Example 1.

[0086] Example 10

[0087] Cellulose, PET plastic, and cellulose mixed with PET plastic (mass ratio 17:3) were subjected to thermogravimetric analysis.

[0088] Embodiment 11

[0089] (1) 10 g of cellulose powder, 10 g of plastic powder, and cellulose powder and plastic powder were mixed in a mass ratio of 15:5 to obtain 10 g of precursor mixture (plastics were PVC, PP, and PET), and the mixture was poured into 50 ml of diammonium phosphate solution (the mass ratio of diammonium phosphate to precursor mixture was 0.01:1) and stirred for 0.2 h;

[0090] (2) drying the mixture obtained in step (1) and carbonizing it at 1300° C. for a certain period of time (2 h) in an argon atmosphere to obtain a hard carbon material;

[0091] (3) Pour the hard carbon material obtained in step (2) into 1 mol of hydrochloric acid, stir and pickle, then wash with deionized water and dry, thereby obtaining a hard carbon negative electrode material for a sodium ion battery.

[0092] Comparative Example 1

[0093] (1) Dry 10 g of PET powder;

[0094] (2) carbonizing the powder obtained in step (1) at 1300° C. for 4 h under an argon atmosphere to obtain a hard carbon material;

[0095] (3) Pour the hard carbon material obtained in step (2) into 1 mol of hydrochloric acid, stir and pickle, then wash with deionized water and dry, thereby obtaining a hard carbon negative electrode material for a sodium ion battery.

[0096] (4) Assemble the sodium ion battery with the sodium ion battery hard carbon negative electrode material prepared above. According to the mass ratio of 80%:10%:10%, weigh 80 mg of biomass hard carbon material powder, 10 mg of conductive carbon black, and 10 mg of carboxymethyl cellulose, add 0.5 ml of deionized water, stir for 15 minutes until it becomes a uniform slurry, use a 100 μm scraper to evenly coat it on the surface of copper (Cu) foil, dry it in a vacuum drying oven at 100°C for 12 hours, cut the Cu foil with active material into disc-shaped negative electrode sheets, and then transfer them to the glove box for use.

[0097] The assembly of the simulated battery was carried out in a MIKROUNA glove box filled with Ar atmosphere, using the prepared carbon material electrode as the negative electrode, commercial electrolyte 1.0 mol / L NaPF6 / EC:DMC:EMC (1:1:1) (V:V:V) as the electrolyte, and Na metal sheet as the counter electrode to assemble a 2032 button cell.

[0098] Comparative Example 2

[0099] (1) 10 g of a precursor mixture was obtained by mixing cellulose powder and PET powder in a mass ratio of 17:3;

[0100] (2) carbonizing the precursor mixture obtained in step (1) at 1300° C. for 4 h under an argon atmosphere to obtain a hard carbon material;

[0101] (3) Pour the hard carbon material obtained in step (2) into 1 mol of hydrochloric acid, stir and pickle, then wash with deionized water and dry, thereby obtaining a hard carbon negative electrode material for a sodium ion battery.

[0102] (4) The hard carbon negative electrode material for sodium ion batteries prepared as above is used as the active material of the negative electrode material for preparing sodium ion batteries, and the specific method is the same as that of Comparative Example 1.

[0103] Comparative Example 3

[0104] (1) Dry 10 g of cellulose powder;

[0105] (2) carbonizing the powder of step (1) at 1300° C. for 4 h under an inert atmosphere to obtain a hard carbon material;

[0106] (3) The hard carbon material obtained in (2) is poured into 1 mol of hydrochloric acid and stirred for pickling, and then washed with deionized water and dried to obtain a hard carbon negative electrode material for a sodium ion battery.

[0107] (4) The hard carbon negative electrode material for sodium ion batteries prepared as above is used as the active material of the negative electrode material for preparing sodium ion batteries, and the specific method is the same as that of Comparative Example 1.

[0108] Table 1 shows the charge specific capacity, discharge specific capacity and first efficiency (current density = 50 mAg) of the hard carbon assembled sodium ion batteries prepared in Examples 1-5 and Comparative Examples 1-3. -1 ).

[0109] Table 1

[0110]

[0111] As can be seen from Table 1, the capacity of pure cellulose and PET is not high, and cellulose has the disadvantage of low initial efficiency of typical biomass hard carbon. However, after mixing the two and co-pyrolyzing them, both the capacity and the initial efficiency are increased. Furthermore, it is difficult to further increase its capacity level by simple physical means. On this basis, we found that adding phosphate has a positive effect on the final capacity of the hard carbon in the co-pyrolysis system.

[0112] Figure 1 The constant current charge and discharge curve of the electrochemical test of the hard carbon assembled sodium ion battery prepared in Example 1 (current density = 50mAg -1 ), it can be seen that the hard carbon obtained by the present invention has excellent performance and meets the commercial level.

[0113] Figure 2 This is the thermogravimetric analysis diagram of cellulose, PET plastic, and cellulose mixed with PET plastic (cellulose:PET plastic=17:3, w / w) in Example 10. It can be seen that the cellulose and plastic interact with each other during the pyrolysis process, and this interaction makes the final hard carbon electrode perform well.

[0114] Figure 3 By comparing the carbon yields obtained by carbonizing cellulose powder, plastic powder, and a mixture of cellulose powder and plastic powder under the same conditions in Example 11 with the carbon yield obtained by theoretical calculation of the mixture of cellulose powder and plastic powder, it can be seen that the carbon yield obtained by co-pyrolysis of the mixture of cellulose powder and plastic powder is much higher than the theoretically calculated carbon yield.

[0115] Figure 4 The nitrogen adsorption-desorption curves of the hard carbon prepared in Example 1 and Example 4 show that co-pyrolysis greatly reduces the specific surface area of ​​the hard carbon finally obtained, and a low specific surface area often results in a higher initial efficiency.

[0116] The above embodiments are preferred implementation modes of the present invention, but the implementation modes of the present invention are not limited to the above embodiments. Any other changes, modifications, substitutions, combinations, and simplifications that do not deviate from the spirit and principles of the present invention should be equivalent replacement methods and are included in the protection scope of the present invention.

Claims

1. A method for preparing a hard carbon negative electrode material for a sodium ion battery by co-pyrolysis of biomass and plastic, characterized in that: The following steps are involved: (1) mixing biomass powder and plastic powder, adding the mixture into a phosphate solution and stirring for 0.2 to 2 hours; (2) drying the mixture obtained in step (1) and carbonizing it under an inert atmosphere; (3) The carbonized product obtained in step (2) is acid-washed, then washed with deionized water and dried to obtain a hard carbon negative electrode material for a sodium ion battery.

2. The method according to claim 1, characterized in that: The biomass powder in step (1) includes cellulose powder or waste agricultural and forestry powder; The plastic powder described in step (1) is at least one of polyethylene terephthalate PET, polypropylene PP, polyvinyl chloride PVC, and polyethylene PE.

3. The method according to claim 2, characterized in that The waste agricultural and forestry materials are at least one of oil tea shells, walnut shells, coconut shells, bamboo, peanut shells, straw and rice husks.

4. The method according to claim 1, characterized in that: The mass ratio of the biomass powder to the plastic powder in step (1) is 19:1 to 1:

1.

5. The method according to claim 1, characterized in that The phosphate described in step (1) is ammonium dihydrogen phosphate; The mass ratio of the phosphate: biomass powder and plastic powder mixture in step (1) is 0.01:1 to 0.5:

1.

6. The method according to claim 1, characterized in that The inert atmosphere in step (2) is nitrogen or argon.

7. The method according to claim 1, characterized in that The carbonization conditions in step (2) are: a heating rate of 0.5 to 20° C. / min, a carbonization insulation temperature of 1100 to 1500° C., and a carbonization insulation time of 0.5 to 10 hours.

8. The method according to claim 1, characterized in that The pickling in step (3) is performed by immersing and stirring in hydrochloric acid with a concentration of 1 to 2 mol / L.

9. A hard carbon negative electrode material for a sodium ion battery, characterized in that: It is prepared by the method according to any one of claims 1 to 8.

10. Use of the sodium ion battery hard carbon negative electrode material according to claim 9 in the preparation of sodium ion batteries.

Citation Information

Patent Citations

  • Reed-derived hard carbon sodium battery negative electrode material, preparation method thereof and energy storage battery

    CN115528232A

  • Biomass hard carbon material, preparation method thereof and application of biomass hard carbon material in sodium ion battery

    CN118270767A

Cited By

  • Biomass-based hard carbon material regulated and controlled by sulfonated aromatic hydrocarbon, preparation method of biomass-based hard carbon material and application of biomass-based hard carbon material in sodium-ion battery

    CN120646807A